Analysis of Value Added of The Processing of Dried Patchouli Leaves Into Patchouli Oil In Mowila District South Konawe Regency - Sahrul Ramadan; Surni Surni; Munirwan Zani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2022)
This study aimed to determine the processing and added value of dried patchouli leaves into patchouli oil in Mowila District, Konawe Selatan Regency. This research was conducted in Mowila District, Konawe Selatan Regency, in March 2022. The research population was patchouli farmers who processed patchouli oil in Mowila District, totaling 20 people, while the research sample used the census method. This study uses primary data and secondary data. Data collection techniques using interviews, observation, and summaries. The research variables include production costs (raw materials, patchouli oil prices, and other input contributions), product value, added value, and labor (wages). This study was analyzed using a qualitative descriptive method and the Hayami method. The results showed that: (1) the processing of dried patchouli leaves into patchouli oil which includes the process of putting water into the dried patchouli leaves into a pot, distillation (evaporation), cooling, filtering water and patchouli oil and packaging patchouli oil; and (2) the processing of dried patchouli leaves into patchouli oil in Mowila District, Konawe Selatan Regency provides an added value of Rp. 499.00/Kg or 94.20%/Production (High Ratio) This business is included in the added value category with a profit of Rp. 222,875, or a ratio of 44.66%.